IMPLEMENTASI MODEL PEMBELAJARAN TEMATIK DAN KOLABORATIF DI KELOMPOK BERMAIN AISYIAH MUTIARA UMMI KALASAN YOGYAKARTA - Maulida Maulida; Nadiyah - Nadiyah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This research uses descriptive qualitative research. The subjects in this study were teachers, principals, school administrators or chairmen of the Aisyiah Play Group Mutiara Ummi Kalasan Yogyakarta Foundation. The technique of collecting data uses observation and interviews. While the instruments used are guidelines for observation and interviews. Data analysis techniques are data reduction, data display and conclusion drawing/verification. The results of this study are the implementation of thematic and collaborative learning models in the Mutiara Ummi Kalasan Yogyakarta Playgroup providing effective and conducive learning outcomes for students. Various activities are implemented by the teacher so that children can collaborate in playing activities with their friends. This process is applied using diverse and unique tools and media. This process also makes students feel comfortable, calm, of course also a fun learning process. The process of applying thematic and collaborative learning models is interrelated and continuous, during the learning process in the classroom and outside the classroom. Keywords: learning models, thematic, collaborative